Gender Moderates the Influence of Self-Construal Priming on Fairness Considerations - Flinkenflogel, Nic; Novin, Sheida; Huizinga, Mariette; Krabbendam, Lydia (Frontiers in Psychology, 2017)
Research in social and cultural psychology has identified that self-construal, or the way the self is defined in relation to others, plays an important role in social decision-making processes. Yet it remains difficult to isolate the effect of self-construal in a comparative approach. Therefore, we used priming methodology in three studies to induce either an independent or interdependent mindset to test direct consequences on fairness considerations. Specifically, we asked whether participants would accept an unfair ultimatum game offer: a split of 10 euros, where the participant is allocated the marginal share of 3 and the proposer 7. If the participant refuses, neither gets paid. In the first study, we used the well-known similarities and differences prime. Here, activating an interdependent mindset decreased rejection of the unfair offer compared to the independent mindset and control condition, but only in females. The prime did not affect males. In the second and third study we modified our university's mission statement to instead include either independent or interdependent values. Females displayed a similar direction of effects; in males however, activating an interdependent mindset increased rejection. Taken together, the results show that whether participants accept or reject an unfair offer depends on both their gender and the self-construal prime. The results were interpreted using the distinction between relational independence that has been associated with females, and collective interdependence, that has been associated with males. Possible consequences for future studies are discussed.